2005–2018 trends in ozone peak concentrations and spatial contributions in the Guadalquivir Valley, southern Spain. (1st June 2021) - Massagué, Jordi; Contreras, Juan; Campos, Alberto; Alastuey, Andrés; Querol, Xavier
Abstract: We assessed 2005─2018 data series of NO, NO2, and O3 surface measurements, meteorological data and remote sensing of tropospheric NO2 by OMI-NASA in the Guadalquivir Valley (GV, Andalucía). The GV is one of the Spanish atmospheric basins with the most exceedances of the EU's hourly O3 information threshold (180 μg O3 m −3 ). We aimed to deepen understanding of the phenomenology of O3 episodes in the GV, quantify local and regional contributions from long-range transported O3, and identify key episodes and atmospheric parameters to validate modeling tools for the assessment of O3 abatement policies with acceptable uncertainty levels. A significant proportion of acute O3 episodes (defined as episodes of 1–7 consecutive days, when very high hourly O3 concentrations are recorded) in the GV is caused by long-range transported contributions in addition to the regional accumulation of pollution which is, in most cases, driven by the vertical recirculation of air masses, as described in several basins of the Iberian Peninsula. In these episodes, high O3 arises from the fumigation of high reserve recirculated strata as the boundary layer grows, sea-breeze transport of O3 and precursors, local formation, and long-range transport. The most acute episodes are recorded close to Sevilla, probably because of the mix of precursors from the urban areas and the petrochemical industry of Huelva. We quantified the average O3 contributions to O3 concentrations in Sevilla during these episodes as 53% background levels before the episode (defined as the concentration measured at the coastal remote sites at the beginning of the pollution episode, when the Atlantic air masses transport background O3 from synoptic air mass transport), 22% accumulation throughout the episode, and 25% of daily local and regional contribution to the average 8h-daily maxima (157 μg O3 m −3 ). Thus, a maximum decreasing potential of 74 μg O3 m −3 (47%) of the average 8h-daily maxima can be expected when applying abatement measures to reduce O3 precursors in the day before the start of an episode and until the end of the episode. Our results demonstrate that it is crucial to meteorologically forecast the occurrence of such recirculation and accumulation processes in the GV basin. Highlights: A 2005─2018 evaluation of high ozone pollution in the Guadalquivir Valley. Frequent ozone accumulation driven by vertical recirculation in the Valley. Information threshold exceeded in Sevilla (>3 h yr −1 ), target value in the Valley (>50 day yr −1 ). Quantification of O3 contributions during the most acute episodes in Sevilla. Significant maximum O3 abatement potential: 47% (74 μg m −3 ) of max 8h-daily concentration.